Allostatic load and chronic pain: a prospective finding from the national survey of midlife development in the United States, 2004–2014 - Liang, Yunlong; Booker, Cara (BMC public health, 2024)
Background Previous research has demonstrated a correlation between chronic stress and chronic pain (CP). However, there have been few studies examining the prospective association of allostatic load (AL)—the biological processes related to stress—with CP. Methods We firstly conducted latent class analysis to identify phenotypes of AL using a community-dwelling sample, the Midlife in the United States. Multinomial logistic regression models were used to examine the prospective association between phenotypes of AL at MIDUS 2 biomarker project and the presence of CP, CP interference and the number of CP sites at MIDUS 3. Results Three phenotypes of AL, low biological dysregulation, parasympathetic dysregulation and metabolic dysregulation, were identified. Compared to low biological dysregulation group, participants experiencing metabolic dysregulation phenotype of AL at MIDUS 2 had higher risks of having high-interference CP (RRR = 2.00, 95% CI: 1.06, 3.79, P < 0.05) and 3 or more CP sites (RRR = 2.03, 95% CI: 1.08, 3.83, P < 0.05) at MIDUS 3. Conclusion The findings indicate that focusing on mitigating the metabolic dysfunction phenotype of AL has the potential to be an efficacious strategy for alleviating future CP bodily widespreadness and high CP interference.